2007
DOI: 10.1021/jp0772225
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ceria-Supported Vanadium Oxide Catalysts during the Oxidative Dehydrogenation of Ethane and Temperature-Programmed Treatments

Abstract: The effect of vanadium oxide loading on CeO 2 support for ethane oxidative dehydrogenation (ODH) is studied. Surface vanadia species are highly dispersed on CeO 2 . The interaction with surface vanadia species significantly changes the structural and reactive properties of ceria support. VO x /CeO 2 suffers an important change during ethane ODH due to a solid-state reaction between CeO 2 and surface vanadia species resulting in the formation of CeVO 4 . Such a solid-state reaction is promoted by high temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 24 publications
6
83
0
1
Order By: Relevance
“…A decline in the peak intensities of a CeVO 4 phase is observed for CV25, which indicates the conversion of V 5+ to V 3+ due to the formation of a CeVO 3 phase. [32,36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decline in the peak intensities of a CeVO 4 phase is observed for CV25, which indicates the conversion of V 5+ to V 3+ due to the formation of a CeVO 3 phase. [32,36].…”
Section: Resultsmentioning
confidence: 99%
“…It is utilized for selective redox reactions in batteries [29] and gas-sensing applications [30,31]. V 2 O 5 supported with SiO 2 , TiO 2 , Al 2 O 3 , MgO, and CeO 2 is also used in the selective oxidation of hydrocarbons for H 2 and CO production [30][31][32][33][34][35]. Consequently, vanadia-ceria tertiary metal oxide systems have been widely studied for their structural, chemical, and oxidative properties [36].…”
Section: Introductionmentioning
confidence: 99%
“…The combination and/or contacting of different metal oxides can, in principle, produce novel structural and/or electronic properties either at the contact sites or in the intersolved zones, which are not seen in single‐metal oxides. Over the years, there has been strong interest in catalysis of mixed‐metal oxides and other multimetal oxides …”
Section: Figurementioning
confidence: 99%
“…Mater. 2011, 23, 5293-5301 showed that the surface vanadia species remain as V 5 + in reducing conditions, which in turn promotes the formation of CeVO 4 by 200 ° C. [ 44 ] A qualitative cartoon of the vanadia-ceria interface presented in 2004 by Martínez-Huerta is presented in Figure 4 A, illustrating the progressive interaction between the ceria support and the surface vanadium oxide species. In 2009, the model of the vanadia-ceria interface [ 19 , 43,44 ] was confi rmed by a DFT study (Figure 4 B).…”
Section: Research Newsmentioning
confidence: 99%
“…In 2009, the model of the vanadia-ceria interface [ 19 , 43,44 ] was confi rmed by a DFT study (Figure 4 B). [ 45 ] Such an interaction stabilized Ce 3 + at the vanadia-ceria interface, [ 43,44 ] and DFT calculations bring the rationale for such a stabilization. [ 45 ] This system constitutes a nice example of the synergetic interaction between operando and theoretical modelling approaches.…”
Section: Research Newsmentioning
confidence: 99%